Corrosion due to ageing influences the performance of tubular platinum microrobots. Issue 3 (3rd January 2018) - Maric, Tijana; Nasir, Muhammad Zafir Mohamad; Wang, Yong; Khezri, Bahareh; Pumera, Martin
Abstract : Storing of platinum micromotors over prolonged period decreases their efficiency due to the corrosion. Abstract : Autonomous self-propelled nano and microrobots are in the forefront of materials research. The micromachines are typically prepared in batches, stored and subsequently used. We show here that the storage of platinum tubular catalytic microrobots in water causes their corrosion which results in their lower mobility and performance. This has important implications for the construction and storage of these autonomous micromotors.